(untitled) (Asian Journal of Medical and Biological Research, 2021)
Char dwellers are considered poorer than the mainland population. A constant threat of riverbank failure, flooding, and seasonal cyclone, combined with lack of physical infrastructures, and employment opportunities in the Chars, makes a vulnerable, difficult, and fragile life. The aim of the present work was an initiative to improve the livelihood of Char dwellers through fish culture in the net cages. A focus group survey was conducted on Char dwellers to know about the livelihood conditions. Quantitative and qualitative analysis of plankton was performed to know the productivity of the Padma River. In the study area, there was an average of 5 household members in each family of the Charland dwellers, and the average sex ratio of males and females was 56.67% and 43.33%, respectively. The age group of below 15 to 60 years and their religion ratio of Muslim and Hindu was 45% and 55%. The total number of identified genera of phytoplankton was 41, and the total number of zooplankton genera was 20 in the Padma River. Tilapia (Oreochromis niloticus) was cultured in the net cages providing three different feeds i.e. natural feed, kitchen waste (leftover rice), and rice bran. The final weights of the experimental tilapia were 314.8 ± 24.3 g after 5 months of feeding natural food, 321.4 ± 22.8 g after 5 months of feeding natural food with kitchen waste, and 324.8 ± 29.5 g after 5 months of feeding natural food with rice bran. Considering the plankton populations and water quality parameters, the Padma River near the Charland of Munshiganj was productive for fish farming. We found the results of Genetically Improved Farmed Tilapia (GIFT) farming in net cages near the river of Char, which were almost the same (has no significant difference among the diets) by providing low-cost supplementary feed and without supplementary feed. Therefore, the result indicates that Char dwellers can culture fishes in net cages to have the fish in their daily meals and can earn extra income from selling the fish to improve their livelihood. Moreover, applied research and interdisciplinary adaptive policy framework are requisite for the Charland livelihoods sustainability in the Padma River, Munshiganj, Bangladesh. Asian J. Med. Biol. Res. 2021, 7 (2), 174-181